2013
DOI: 10.1371/journal.pone.0075528
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Investigation of the Membrane-Disrupting Mechanism of the Antimicrobial and Amyloid-Like Peptide Dermaseptin S9

Abstract: Dermaseptin S9 (Drs S9) is an atypical cationic antimicrobial peptide with a long hydrophobic core and with a propensity to form amyloid-like fibrils. Here we investigated its membrane interaction using a variety of biophysical techniques. Rather surprisingly, we found that Drs S9 induces efficient permeabilisation in zwitterionic phosphatidylcholine (PC) vesicles, but not in anionic phosphatidylglycerol (PG) vesicles. We also found that the peptide inserts more efficiently in PC than in PG monolayers. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 57 publications
4
44
0
Order By: Relevance
“…It was reported previously that human AMP LL‐37 can naturally oligomerize at physiological pH into nanoparticles to resist the action of proteases . In past years, several studies have reported the self‐assembly phenomenon of AMPs . Our group has previously reported the formation of amyloid‐like assemblies by a plant AMP .…”
Section: Introductionmentioning
confidence: 78%
“…It was reported previously that human AMP LL‐37 can naturally oligomerize at physiological pH into nanoparticles to resist the action of proteases . In past years, several studies have reported the self‐assembly phenomenon of AMPs . Our group has previously reported the formation of amyloid‐like assemblies by a plant AMP .…”
Section: Introductionmentioning
confidence: 78%
“…Consequently, this study supports the hypothesis that amyloidogenic aggregation of peptides is a pathway that provides active and novel antimicrobials. Potentially, pathological disorders might result from aberrant behaviour or improper regulation of this amyloid‐mediated antimicrobial action …”
Section: Resultsmentioning
confidence: 99%
“…A beguiling hypothesis is that amyloidogenic peptides are antimicrobial, host‐defense peptides . In accordance with this, amyloidogenic peptides and antimicrobial peptides (AMPs) share the ability to bind to/within a cell membrane inducing a similar permeation (barrel‐stave or toroidal pores) or disruption (carpet or detergent effect) of the membrane, while doing so via potentially different mechanisms .…”
Section: Introductionmentioning
confidence: 97%
“…Indeed, the specificity showed by Cm‐p5 is in accordance with its condition to be nontoxic for mammalian cells. It is noteworthy that the antibacterial peptide dermaseptin S9 (similar nonamphipatic pattern regarding Cm‐p5) inserts less efficiently in phosphatidylglycerol than in phosphatidylcholine monolayers (54). This behavior is in contrast with the specificity showed by Cm‐p5.…”
Section: Discussionmentioning
confidence: 99%